Evidence Based Medicine: Clinical Trials - L Kashani; R Hajiaghaee; S Akhondzadeh (Institue of Medicinal Plants, ACECR, 2014)
Evidence based medicine is very important for success of modern medicine. It is the ongoing process of using the most reliable evidence from clinical studies, scientific understanding and medical practice to make the best possible medical choice for patients. Evidence based medicine is how medicine advances and how we get improvements in life expectancy and quality of life. It not only identifies which treatments are effective but also those which are ineffective and may do more harm than good, and identifies areas where more investigation is needed and where there may be gaps in knowledge. In this review we focus on clinical trials.